Reframing Islamic Education to Resist Social Prejudice: A Critical Study on Stereotypes, Ethnicity, and Educational Transformation in Indonesia - Murdianto (International Journal of Social Sciences and Humanities, 2025)
This research is motivated by the still strong social prejudices and ethnic stereotypes in Indonesia's multicultural society. Islamic education has basic values that are relevant to answer these problems, such as justice, ukhuwah, compassion, deliberation, and respect for human dignity. However, these values are often still taught normatively and have not been fully associated with the social reality of students. This research aims to analyze how Islamic education can be reframed as a space of resistance to social prejudices, ethnic stereotypes, and discriminatory social relations. This study uses a qualitative approach with a secondary data-based literature study. Data were obtained from scientific journal articles, academic books, research reports, policy documents, statistical data, and official publications relevant to Islamic education, ethnic stereotypes, multicultural education, religious moderation, and educational transformation. Data are analyzed using qualitative content analysis and thematic analysis to find categories, patterns of meaning, and key themes in the document. The results of the study show that social prejudices and ethnic stereotypes are formed through long social processes, such as inheritance of family narratives, community environment, media, historical experiences, and limited intergroup interaction. In the educational space, prejudice can be present through the teacher's language, learning examples, relationships between students, and school culture. The findings also show that Islamic education can be a space for transformation if Islamic values are linked to social identity theory, intergroup contact, multicultural education, critical pedagogy, and hidden curriculum. This study concludes that Islamic education needs to be directed to be inclusive, critical, and transformative education. The transformation must touch the curriculum, teachers, learning strategies, and school culture so that Islamic education is able to form students who are religious, fair, reflective, and free from social prejudice.